Promoting recovery in long-term institutional mental health care: an international Delphi study - Turton, P (2010)
OBJECTIVE: Service provision in psychiatric and social care is increasingly guided by recovery principles. However, little is known about the degree of consensus among stakeholders in diverse contexts on the components of care that most promote recovery. This study aimed to identify specific items of care that key stakeholders regard as most important in promoting recovery for people with longer-term mental health problems in institutional care, to measure consensus between and across stakeholder groups and countries, and to develop a conceptual framework of the most important domains of care. METHODS: Ten European countries in various stages of deinstitutionalization participated in a series of conventional three-round iterative Delphi exercises. In each country individuals in four separate expert groups (service users, mental health professionals, caregivers, and advocates) identified components of care that they considered important to recovery and then rated their group's suggestions in terms of importance. Median and consensus ratings were measured. High-ranking items were grouped into domains. RESULTS: A total of 4,098 separate items of care were proposed by the 40 participating groups. Eleven broad domains of care important for recovery were identified: social policy and human rights, social inclusion, self-management and autonomy, therapeutic interventions, governance, staffing, staff attitudes, institutional environment, postdischarge care, caregivers, and physical health care. Consensus between groups and countries was generally high, but some modest differences in priorities were noted. CONCLUSIONS: The most consistently highly rated consensus domain was therapeutic interventions. Domains and components of care related to recovery principles were also viewed as important across stakeholder groups.